Public Perception of the Existence of Beef Cattle Farms in Central Lampung Regency, Lampung Province - Purnomo, Purnomo; Herdiansah, Riko; Setiyowati, Sari; Agustiana, Elia (Formosa Journal of Applied Sciences, 2023)
The aim of this research is to determine the public's perception of the existence of beef cattle farming. The research was carried out in July 2023. The method used in this research was a survey method, namely taking a direct approach to the community around the location of the livestock business. Research data analysis uses descriptive statistical analysis using grouping, presentation and simplification of data using frequency distribution tables and using Likert scale measurements. The results of the research are that some people feel disturbed by the existence of cattle farming businesses because of the lack of cleanliness of these farms, which causes unrest in the community. The results obtained for the odor sub-variable are in the agree category. The results of these scores show that according to the respondents' answers, only some respondents felt that there was a change in the color of the water and the water smelled, only people who were closer to the farm.